Characterization of laser-driven proton beams from near-critical density targets using copper activation. (5th September 2014) - Willingale, L.; Nagel, S. R.; Thomas, A. G. R.; Bellei, C.; Clarke, R. J.; Dangor, A. E.; Heathcote, R.; Kaluza, M. C.; Kamperidis, C.; Kneip, S.; Krushelnick, K.; Lopes, N.; et al.
Abstract : Copper activation was used to characterize high-energy proton beam acceleration from near-critical density plasma targets. An enhancement was observed when decreasing the target density, which is indicative for an increased laser-accelerated hot electron density at the rear target-vacuum boundary. This is due to channel formation and collimation of the hot electrons inside the target. Particle-in-cell simulations support the experimental observations and show the correlation between channel depth and longitudinal electric field strength is directly correlated with the proton acceleration.